Professional Training in Educational Sports in Brazil: The Collaborating Teams of the Programa Segundo Tempo (PST) – Federal Government (Research, Society and Development, 2022)
PST is a public educational sport policy of the Brazilian Federal Government for the promotion of educational sports by the Ministry of Sport (2003-2018) with the support of the Collaborating Teams. The purpose of this article is to describe who these teams were, how educational sport was thought of by them, and how these Collaborating Teams approached teachers of Physical Education who worked in educational sport centers (Core Coordinators). For description and analysis, we used the literature review with the subject of professional training, educational sport and Programa Segundo Tempo [Second Time Program] and we count on documental analysis by Bardin (2011). We have conclude that the Collaborating Teams show the possibility of intervening in the training of Core Coordinators throughout the country, and for that, these Teams were formed by trainers (university professors) who worked in the search for dialogue with the Coordinators of Sports Core. This dialogue has the potential to reinvent sport, from a traditional sport to an educational sport aiming to ensure the rights of children and adolescents to access sport and leisure in Brazil.